Callas and the Hologram: A Live Concert with a Dead Diva (Sound Stage Screen, 2022)
In this paper, I investigate Callas in Concert, a multimedia show that employs holographic digital and laser technology to bring the legendary diva back to the stage almost 50 years after her death. The aim of the spectacle, which bears witness to the persistence of the Callas cult to the present day, is to allow audiences to see and listen to a digitally manipulated reproduction of the dead singer’s body and voice. At the same time, Callas in Concert is a live concert, where an orchestra performs in front of an audience. My interest lies in two interrelated issues. The first concerns the question as to whether the visual or the aural dimension takes the lead in the attempt to fictionally resurrect a dead singer as a live performer. The second revolves around the paradox inherent in the use of digital technologies of reproduction and remediation to emphasize the peerless uniqueness of Maria Callas’s artistry. In bringing together these two issues, my ultimate goal is to shed light on the artistic nuances and ideological assumptions that pervade the fascination with operatic liveness today.